Food security problem and its evolution (International relations and international law Journal, 2016)
A certain of level of food security has always been among major goals of society and individual with a survival instinct in its core determining whole variety of human activity. Contemporary situation with global food is a specific challenge for lifes of humanity at whole. Rapid growth of Earth population aggravates the problems of food supply. Thus, food crysis and its prevention is one of the main problems of world community’s concern. All around the World food security is basis for national security. No nation can sustain political, economic and national security without providing foof security for its population. Agriculture is not only one of spheres of Economy, but it also guarantee of nation’s food security. In absence of national food industry all other areas of national security will become insignificant.
Keywords: food security; global food security; UN; FAO; Rome declaration; millenium development goals